2020
DOI: 10.3390/coatings10020098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Modification by Means of Low-Temperature Plasma Nitriding on Wetting and Corrosion Behavior of Austenitic Stainless Steel

Abstract: Low-temperature nitriding of austenitic stainless steels produces modified surface layers, consisting mainly of the S phase, which improve surface hardness and corrosion resistance. Because of the localized plastic deformations, owing to modified layer formation, and ion bombardment occurring during the process itself, this treatment produces also modifications of surface morphology and roughness, which can affect wettability and corrosion behavior. In this study the effects of plasma nitriding, performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…The highest CA values were registered for samples subjected to a low pressure process, similar to cathodic sputtering performed with a N-containing atmosphere, and CA as high as 110 • was measured on samples with a 2D finishing. In spite of the low hydrophilicity, and even hydrophobicity, shown by all the nitrided samples types, when liquids having a low surface tension, as ethanol and rapeseed oil, were used as probe, very low CA values were registered, suggesting an oleophilic behavior [127].…”
Section: Wetting Behaviormentioning
confidence: 90%
See 3 more Smart Citations
“…The highest CA values were registered for samples subjected to a low pressure process, similar to cathodic sputtering performed with a N-containing atmosphere, and CA as high as 110 • was measured on samples with a 2D finishing. In spite of the low hydrophilicity, and even hydrophobicity, shown by all the nitrided samples types, when liquids having a low surface tension, as ethanol and rapeseed oil, were used as probe, very low CA values were registered, suggesting an oleophilic behavior [127].…”
Section: Wetting Behaviormentioning
confidence: 90%
“…Martinesi et al [223] reported an increase of CA from 72.8 • to 82 • after plasma nitriding at 400 • C and 500 Pa, but a decrease to 71 • , when the nitrided samples were subjected to a sterilization procedure with ethanol and incubation with 2.5 mM/mL acetic acid for 24 h, while no significant changes were observed for untreated specimens. An increase of apparent CA values for AISI 202 samples, having a polished or a 2D finishing, was observed after nitriding with different conditions, when 0.5 and 3 µL drops of bi-distilled water or a solution of 3.5% NaCl were used [127]. The highest CA values were registered for samples subjected to a low pressure process, similar to cathodic sputtering performed with a N-containing atmosphere, and CA as high as 110 • was measured on samples with a 2D finishing.…”
Section: Wetting Behaviormentioning
confidence: 98%
See 2 more Smart Citations
“…Known works consider the possibility of application of gas discharges technique in the field of thin films deposition, metals surfacing, treatment and modification of metals before welding [2][3][4][5]. Still, as practice has shown, diffusion welding [6] and thermal and chemical-thermal surface treatment [7] are the most appropriate. This is due to the high technological capabilities of the glow discharge, which in these processes can serve both a processing tool and a source of thermal energy for their implementation simultaneously.…”
Section: Introductionmentioning
confidence: 99%